Monocyte distribution width in the detection of sepsis and prediction of mortality in critically ill patients - Soo, Ki Yang; Ramly, Nur Fariza; Md Ralib, Azrina; Liew, Ee Siung; A.Talib, Norlelawati; Mat Nor, Mohd Basri (Kugler Publications, 2022)
Introduction: Sepsis is the leading cause of intensive care unit (ICU) admission. Delayed recognition of sepsis is associated with increased morbidity and mortality. Monocyte distribution width (MDW) represents the width of a set of monocyte volume values, which increases as infections progress in severity. This study evaluated the diagnostic and prognostic accuracy of MDW and white cell count (WCC) for sepsis and mortality. Methods: This was a prospective cohort study of 100 patients who were grouped into sepsis and non-sepsis according to the Sepsis-3 definition. MDW and WCC were collected on admission to ICU and for the subsequent 3 days. Results: On admission, MDW was diagnostic of sepsis with an AUC of 0.86 (95% CI, 0.7–0.94) with a cut-off threshold of 20.97. Serial MDW on days 1 and 2 were also shown to be predictive of sepsis. MDW has a high sensitivity of 92.1% (95% CI, 82.4–97.4%) but a specificity of only 68.8% (95% CI, 50.0– 83.9%). The positive predictive value and negative predictive value of MDW using the new cut-off threshold in this studywere found to be 83.6% (95% CI, 73–91.2 %) and 81.5% (95% CI, 61.9–93.7%), respectively. Conclusions: MDW is an effective screening tool in the detection of sepsis upon admission to the ICU. As part of the differential in some complete blood count analysis machines, MDW provides a cost-effective and widely available test at present. Early detection of sepsis allows initiation of sepsis care bundle and better clinical outcomes.